2014
DOI: 10.1175/jcli-d-13-00456.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Middle and Upper Tropospheric Cooling over Central Asia on the Summer Rainfall in the Tarim Basin, China

Abstract: The changes in summer rainfall over the Tarim Basin, China, and the underlying mechanisms have been investigated using the observed rainfall data at 34 stations and the NCEP–NCAR reanalysis data during the period of 1961–2007. Results show that the summer rainfall over the Tarim Basin, which exhibits a significant increasing trend during the last half century, is closely related to the summer middle and upper tropospheric cooling over central Asia. Mechanism analysis indicates that the middle and upper troposp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 33 publications
6
90
0
Order By: Relevance
“…The anomalous southwesterly wind associated with the trough pattern over CA can further transport the moist air originated from the IO into CA for generating more summer rainfall. This is the so-called twostep process as revealed in Zhao et al (2014). Figure 2b further shows the correlations between volumetrically integrated atmospheric precipitable water from the ERA-40 reanalysis to the same area-averaged SSTs used in Fig.…”
Section: Observed and Model-simulated Linkages Between Io Ssts And Camentioning
confidence: 77%
See 4 more Smart Citations
“…The anomalous southwesterly wind associated with the trough pattern over CA can further transport the moist air originated from the IO into CA for generating more summer rainfall. This is the so-called twostep process as revealed in Zhao et al (2014). Figure 2b further shows the correlations between volumetrically integrated atmospheric precipitable water from the ERA-40 reanalysis to the same area-averaged SSTs used in Fig.…”
Section: Observed and Model-simulated Linkages Between Io Ssts And Camentioning
confidence: 77%
“…Meanwhile, rainfall also has experienced an increased trend over CA (Chen et al 2011). Some observational studies suggested that summer rainfall over CA could be closely related to the SST anomalies in IO, with moist air being transported to CA under suitable circulations (Yang et al 2010;Bothe et al 2012;Zhao et al 2014;Zhou et al 2015). In order to confirm the relationship, we have firstly analyzed the correlations between the summer rainfall over CA and SSTs in IO in 25 CMIP5 models in their historical experiments for the period of .…”
Section: Conclusion and Discussionmentioning
confidence: 97%
See 3 more Smart Citations